Prognostic significance of Naples prognostic score in operable renal cell carcinoma - Wang, Yaohui; Hu, Xu; Zheng, Danxi; Shao, Yanxiang; Lia, Thongher; Li, Xiang (Frontiers in Surgery, 2022)
Background: Naples prognostic score (NPS), a novel scoring system based on nutritional and inflammatory status, is associated with prognosis in several cancers. This study aimed to evaluate the prognostic significance of preoperative NPS in patients undergoing nephrectomy. Patients and Methods: This study retrospectively analyzed patients with renal cell carcinoma (RCC) who underwent radical or partial nephrectomy between 2010 and 2013. The clinicopathological characteristics of patients stratified by preoperative NPS were compared. Survival analysis was performed using the Kaplan-Meier method and log-rank test. Univariate and multivariate Cox proportional hazards models were used to identify independent prognostic factors. Receiver operating characteristic (ROC) curves were used to evaluate prediction efficiency. Results: A total of 638 patients with operable RCC were included. The high-NPS group (NPS group 2) was significantly associated with older age (P < 0.001), larger tumor size (P < 0.001), worse pathological T stage (P < 0.001), positive lymph node pathology (P = 0.002), higher tumor grade (P < 0.001), and greater tumor necrosis (P < 0.001). Multivariable analysis demonstrated that the high-NPS subgroup had significantly worse overall survival (OS) (hazard ratio (HR): 2.25, 95% confidence interval (CI): 1.45–3.50, P < 0.001) and progression-free survival (PFS) (HR: 2.26, 95% CI: 1.48–3.44, P < 0.001). Among several preoperative scoring systems, NPS had the strongest discriminatory power for predicting OS and PFS. Conclusion: Preoperative NPS can serve as a simple novel risk stratification tool to optimize the prognosis of patients with operable RCC. Further prospective and large-scale studies are needed to validate our findings.